Assessing Theory and Practice in Competitive Strategy: Challenges and Future Directions - Parnell, John A. (2008)
Competitive strategy scholars seek to answer three important questions: (a) what constitutes an effective strategy and how is it crafted, (b) how are strategies implemented in an organization, and (c) how can a strategy’s effectiveness be evaluated? Three corresponding themes, namely, strategy formulation, execution or implementation, and evaluation or control, permeate the competitive strategy literature. In this paper, nine issues of scholarly and practical relevance in the competitive strategy domain are reviewed and assessed. Collectively, the nine issues reflect the significant progress made in competitive strategy research in recent years and opportunities for further development in the field. Directions for future research are discussed.